Academic partnership in NLS resource design: a European case study. - Jo Pye (Information Research: An International Electronic Journal)
This paper describes the library work package of the European Unions Telematics for Teacher Training project, which links the Libraries and Education and Training sectors. Its two major deliverables, a user needs analysis report addressing networked learner support in European partner institutions and development of an online course for librarians, are discussed in terms of professional development opportunities for partnership between academic and information staff.